2016
DOI: 10.1021/acscatal.6b00302
|View full text |Cite
|
Sign up to set email alerts
|

FIB-SEM Tomography Probes the Mesoscale Pore Space of an Individual Catalytic Cracking Particle

Abstract: The overall performance of a catalyst particle strongly depends on the ability of mass transport through its pore space. Characterizing the three-dimensional structure of the macro- and mesopore space of a catalyst particle and establishing a correlation with transport efficiency is an essential step toward designing highly effective catalyst particles. In this work, a generally applicable workflow is presented to characterize the transport efficiency of individual catalyst particles. The developed workflow in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 61 publications
3
54
0
Order By: Relevance
“…Similarly, the analyzed particles possess near identical interfacial areas of feed-transporting pores with zeolite elements. If such global metrics were applicable, both samples should possess a similar functional capacity 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the analyzed particles possess near identical interfacial areas of feed-transporting pores with zeolite elements. If such global metrics were applicable, both samples should possess a similar functional capacity 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Martinez et al 27 extended these observations to other impurities, including nickel and the zeolite-poisoning vanadium and sodium. Structural studies of the pore network 1 , 15 , 20 , 28 further revealed the clogging of diffusion highways by metal-rich impurity deposits 16 , 29 , 30 and, importantly, the pore network’s persistent integrity even after deactivation 31 . Based on these observations, permanent catalyst deactivation is currently postulated to arise in part from the obstruction or removal of diffusion highways close to the particle exterior 15 , 16 , 32 , 33 .…”
Section: Introductionmentioning
confidence: 99%
“…[18,19] During the FCC process, the catalyst deactivates irreversibly due to dealumination and the accumulation of metals, mainly Fe, Ni, and V. While Ni and V decrease the yield by promoting for example, coke formation, Fe is supposed to deactivate the particles by creating a shell of reduced porosity on the particles outer surface, either via vitrification of the particle matrix in the presence of Fe and/or co-deposition of silica. [20][21][22][23][24][25][26][27][28][29] Therefore, during operation, to create a stable process efficiency, a fraction of catalyst is being replaced on a daily basis, resulting in a mixture called equilibrium catalyst (ECAT). To investigate their deactivation, FCC ECAT particles are often sorted based on their skeletal density, which is associated with metal loading and age.…”
Section: Recent Advances In Microfluidics Open New Ways To Workmentioning
confidence: 99%
“…This results in a large fraction of accessible gold surface atoms, particularly at kink and step sites, which makes np‐Au very interesting for catalysis and sensing applications . As with all functional materials, it is important to understand physical characteristics such as surface area, porosity, shape and mechanical stability, in order to: (i) define structure–activity relationships; (ii) identify and control synthesis parameters which lead to such structures; (iii) design future catalysts for target applications . When applied to catalysis, analytical methods based on structural imaging or microscopy are therefore required to incorporate large fields of view, high spatial resolution, and to extend across multiple length scales .…”
Section: Introductionmentioning
confidence: 99%